A comparative analysis of dual‐axis implants placed into maxillary anterior extraction sockets versus virtual planning with uniaxial implants: A simulated cone beam computed tomography study of implant length and diameter. Issue 1 (11th January 2023) - Song, Seung Jun; Chu, Stephanie M.; Chu, Stephen J.; Saito, Hanae; Levin, Barry P.; Egbert, Nicholas L.; Sarnachiaro, Guido O.; Tarnow, Dennis P.
Abstract: Objective: The biaxial nature of the anterior maxilla poses a surgical and restorative challenge in implant dentistry. The present study sought to investigate the apical socket perforation rate (ASPR) from a simulated uniaxial implant placement and to determine the effect of implant length and diameter on ASPR when a uniaxial implant was placed compared with the orientation of the pre‐existing dual‐axis implant. Material and Method: Cone beam computed tomography (CBCT) scans from the database of three private practices were searched for patients who received dual‐axis implants within the esthetic zone in immediate tooth replacement therapy. A uniaxial implant was virtually placed using the pre‐existing screw access channel of the dual‐axis implant as a reference. The closest length and diameter were selected for the simulated implant. ASPR by the uniaxial implant was recorded. In addition, the affordable maximum length of a corresponding uniaxial implant that would avoid apical socket perforation was measured. Result: Eighty‐one patients with a total of 101 dual‐axis dental implants were selected for analysis. A simulated virtual surgical planning with uniaxial implants revealed high ASPR (48.51%). When the length of the uniaxial implant was reduced to 11 and 9 mm, ASPR was decreased to 41.58% and 20.79%, respectively. Conclusion: Dual‐axis implant design effectively evades anatomical challenges in the anterior maxilla (esthetic zone). Considering the current evidence, efforts should be made to carefully consider the angular disparity between the extraction socket‐alveolus complex and the future restorative emergence so that a harmonious biologic‐esthetic result may be more predictably and consistently obtained.